2004
DOI: 10.1016/j.rapm.2004.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal mepivacaine and prilocaine are less neurotoxic than lidocaine in a rat intrathecal model

Abstract: It is suggested that intrathecal mepivacaine and prilocaine are less neurotoxic than highly concentrated lidocaine in a rat intrathecal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…28,29 These findings are comparable with the clinical pictures of transient neurologic symptoms in which only sensory symptoms have appeared.…”
supporting
confidence: 78%
“…28,29 These findings are comparable with the clinical pictures of transient neurologic symptoms in which only sensory symptoms have appeared.…”
supporting
confidence: 78%
“…8,11 The results also showed that the area most sensitive to the neurotoxic effects of the aforementioned agents was identical; axons on the posterior root just at entry into the spinal cord (entry zone). [8][9][10][11] Although NaHSO 3 has been used as an antioxidant additive most frequently with chloroprocaine, we have not yet investigated the neurotoxicity of chloroprocaine on posterior root axons. For this reason, we used mainly procaine and additionally chloroprocaine in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] These reports correspond to our previous results, indicating that intrathecal anesthetics affected posterior column and produced gait disturbance with intact motor system in rats. [8][9][10][11] If intrathecal anesthetics affected dorsal column by blocking Aβ fiber, our cultured model examined the effect of local anesthetics on the axon projecting from large type DRG neurons and might reflect the effects of local anesthetics in the clinical setting. Moreover, NaHSO 3 enhanced chloroprocaine effects on the axon in our experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After fixation, the lumbar spinal cord with the anterior and posterior roots (PRs) and the cauda equina were removed en bloc and dissected into 4 samples: transverse section with both roots of L3, posterior or anterior roots just proximal to the dorsal ganglion, and cauda equina nerves for light and electron microscopic examinations, as described in our previous study. 12 All specimens were embedded in epoxy resin. The semithin sections (0.5Y1.0 Km thick) were stained with polychrome dyes.…”
Section: Tissue Preparationmentioning
confidence: 99%